Sustainable Entrepreneurship: Opportunities and Challenges in the Gambian energy sector - Abdoulie, Harding (2015)
The aim of this management project is to investigate critically, the challenges and opportunities associated with the development of renewable energy technology in the Gambia. The essence of entrepreneurism was explored and critically discussed as it provided the conceptual hegemony from which other related concepts discussed in the literature review emerge. A conceptual framework of the entire dissertation topic is developed in order to ensure the discussion stays with the relevant topic. A striking feature of the discussion from the literature review is that the concept of renewable energy is relatively nascent in academic circles hence consensus on some concepts is difficult to arrive at. More so, in practical terms, there exist gaps in relation to the requisite technology and know-how in order to bring down costs and enable such technologies to be more readily accessible to more entities. This challenge becomes more complex when applied within the Gambian context. Government budgetary constraints coupled with gaps in know-how with regards to renewable energy technologies makes it a difficult terrain for potential investors. With a renewable energy policy barely 7 years into its enactment, roughly 8 RE firms are actively operating – mostly in the rural areas. In an attempt to deconstruct the policy-investment nexus that pertains in the Gambia, a research study was conducted focusing on key policy makers as well as investors active in the Gambian renewable energy sector. The outcomes of the research study are that significant capital investments remain a barrier in investing in renewable energy in the Gambia. Coupled with this, capacity from government and other stakeholders need to be further developed if significant progress can be registered with regards to proliferation of renewable energy technologies in the country. To this end, some solutions have been proposed to advance the renewable energy agenda in the Gambia: adopting a two-pronged approach by utilising geothermal source of energy and solar. Given the abundance of sunshine, solar photovoltaic (PV) units can provide a useful energy source. With the intense heat generated from sunlight, the Gambia potentially stands to benefit from converting this heat to provide a geothermal energy source. These two energy sources can then be combined with wind energy technologies especially along the coastlines to complement the energy required for accelerated and sustainable development. It is apparent that given the heavy dependence of most consumers on fossil fuel and biomass to generate energy in the Gambia, it will take some time for attitudes to change and for these consumers to be weaned off from using such conventional energy sources. The effective education and sensitisation of the general population is crucial if the development of RE technologies in the Gambia is to be advanced.